Impact of parental perinatal depressive and anxiety symptoms trajectories on early parent‑infant impaired bonding: a cohort study in east and west coasts of Malaysia - Nasreen, Hashima E; Pasi, Hafizah; Md Aris, Mohd Aznan; Ab Rahman, Jamalludin; Mohd Rus, Razman; Edhborg, Maigun (Springer Vienna, 2021)
The association between maternal depressive and anxiety symptoms and impaired bonding with infants were widely studied, but not in fathers and none in Malaysia. We investigated the impact of different trajectories of perinatal depressive and anxiety symptoms on parent-infant impaired bonding during 2–3 months postpartum in both mothers and fathers in two areas of Malaysia. This study originated from a psychiatric morbidity cohort study carried out in health clinics in east and west Malaysia. Edinburgh Postnatal Depression Scale and anxiety subscale of Depression, Anxiety, and Stress Scale at late pregnancy and 2–3 months postpartum and Postpartum Bonding Questionnaire were completed by 566 mothers and 457 fathers. About 11.7% mothers and 16.1% fathers reported depressive symptoms during pregnancy, 6.5% mothers and 10.5% fathers during 2–3 months postpartum, and 3–4% mothers and fathers both depressive and anxiety symptoms 2–3 months postpartum. The mean impaired bonding score was highest in mothers and fathers who had both depressive and anxiety symptoms 2–3 months postpartum. Impaired bonding is associated with higher EPDS and DASS (anxiety subscale) scores 2–3 months postpartum in both parents. Physical partner violence and deteriorated marital relationship were associated with increased risk of impaired bonding in mothers. The association between depressive, anxiety, and comorbidity of depressive and anxiety symptoms in both mothers and fathers and parent-infant impaired bonding during 2–3 months postpartum urges for screening and treatment of depressive and anxiety symptoms in both parents during early parenthood.